IPTEKS TEKNOLOGI INFORMASI TERHADAP PENGELOLAAN OPERASIONAL PADA PT. BANK SULUTGO - Suparno, Ribka M. R.; Pabunna, Adriana Nia; Ilat, Ventje (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
IT development is very necessary in a company. Given the many conveniences provided with technological developments. PT. Bank SulutGo also participates in developing IT parts in order to compete in this digital era. In the world of business technology gives a lot of changes. Companies that are unable to keep up with technological developments will find it difficult to maintain their business. In this journal, we will discuss the role of IT in Bank SulutGo. Specifically, it discusses the impact given in operational management. The reliability of the information system supports the operational success of a company. The operational part in question is transaction and administration, accounting, and monitoring and maintenance. The method used in this journal is the SWOT analysis. By implementing measures such as harmonizing information technology, obtaining benefits, risk management, managing resources, and measuring performance.Keywords: Information Technology (IT), Operational Management, SWOT Analysis